IMPLEMENTATION OF THE EU TEMPORARY PROTECTION DIRECTIVE FOR UKRAINIAN REFUGEES: A COMPARATIVE ANALYSIS OF MEMBER STATE RESPONSES - Jikia, Mariam (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
Russia's military invasion of Ukraine on February 24, 2022, triggered the first activation of the European Union's Temporary Protection Directive (TPD) since its establishment in 2001. The present article examines the implementation of Council Directive 2001/55/EC across EU member states in response to the mass influx of Ukrainian refugees. The research analyzes the legal framework governing temporary protection, investigating its practical application and the challenges encountered during implementation. The activation of the TPD marked a significant shift in EU migration policy, providing immediate protection to Ukrainian refugees without requiring lengthy asylum procedures. The study employs a comparative analysis of member state responses, examining countries including mostly Eastern European countries such as Hungary, Romania, and Bulgaria. The research identifies three primary areas of solidarity mechanisms: financial support through EU funds, monitoring and coordination via the Solidarity Platform, and assistance with intra-EU mobility. Implementation challenges included labor market integration difficulties, healthcare access barriers, educational system constraints, and administrative bottlenecks. Despite these obstacles, the TPD activation demonstrated unprecedented European solidarity while highlighting the need for improved coordination mechanisms and standardized implementation procedures to ensure effective protection for displaced populations in future crises.